2020
DOI: 10.1016/j.matdes.2019.108354
|View full text |Cite
|
Sign up to set email alerts
|

Freestanding and flexible composites of magnetocaloric Gd5(Si,Ge)4 microparticles embedded in thermoplastic poly(methyl methacrylate) matrix

Abstract: The implementation of processed magnetic materials onto thermoplastics can be an approach for practical application of brittle intermetallic materials with the advantage of enlarging the range of applications. In the present work, we evaluate the effect of blending magnetocaloric Gd 5 Si 2.4 Ge 1.6 micrometric particles with 3.4 µm in different weight fractions onto a flexible, transparent and non-magnetic poly(methyl methacrylate) (PMMA). A close to homogeneous grain distribution along the polymer surface wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…on near-room-temperature working MC materials for this review article [146][147][148][149][150]. Gd, or Gadolinium, is the representative material for a room-temperature MC material because it has a high magnetocaloric effect of 7.6 μ B per atom near room temperature (since Curie temperature of Gd is 294 K).…”
Section: Magnetocaloric-based Thermal Managementmentioning
confidence: 99%
“…on near-room-temperature working MC materials for this review article [146][147][148][149][150]. Gd, or Gadolinium, is the representative material for a room-temperature MC material because it has a high magnetocaloric effect of 7.6 μ B per atom near room temperature (since Curie temperature of Gd is 294 K).…”
Section: Magnetocaloric-based Thermal Managementmentioning
confidence: 99%
“…A similar trend is reported for different polymer nanocompo- sites. 37,38 Moreover, this interaction moderately adjusts the divalent (Zn 2+ , Cu 2+ ) and trivalent (Fe 3+ ) cation distributions, the lattice constant, and oxygen position parameter compared to the pure ZCF NPs. On the other hand, the crystallite size and lattice parameter "a" and "b" values of PVDF-HFP increase upon composite formation by retaining the same "c" value (see Table 1 and Supporting Information Tables S1− S4).…”
Section: Structural Analysismentioning
confidence: 99%
“…A review of the anticipated applications for magnetocaloric systems suggests that lightness (or portability), mechanical and chemical stability, flexibility, ease of processing, and tunable geometries are key properties that will facilitate implementing these materials in real life refrigerators and waste heat energy harvester devices. …”
Section: Introductionmentioning
confidence: 99%
“…Typically, researchers employ either a top-down or bottom-up approach. The design of polymeric composite films with magnetocaloric inclusions using solvent-casting techniques has led to promising results. , In particular, an interesting report on magnetocaloric microparticles embedded in the poly­(methyl methacrylate) matrix showed that the thermoplastic polymer could affect the particles, acting as a pressure cell and leading to a reduction of the magnetocaloric effect of the system . Concerning polymers, poly­(vinylidene fluoride) (PVDF) is a well-known EA polymer that has different crystallographic phases (α, β, γ, δ, and ε) influenced by C–H–F formation .…”
Section: Introductionmentioning
confidence: 99%